Crystals, methods of preparation and uses of nitrogen-containing heterocyclic compounds

JP2025505801APending Publication Date: 2025-02-28SHANGHAI PHARMACEUTICALS HOLDING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024548614
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-17
Filing Date
2023-02-17
Publication Date
2025-02-28

Smart Images

  • Figure 2025505801000001_ABST
    Figure 2025505801000001_ABST
Patent Text Reader

Abstract

The present invention discloses a crystal, preparation method and use of a nitrogen-containing heterocyclic compound. The present invention provides a C-type crystal of compound 1, and discloses its preparation method, composition and use in the manufacture of a medicament. The crystal has high stability and good bioavailability. [Formula 1] JPEG2025505801000030.jpg40169
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims priority to Chinese patent application No. 2022101475924, filed on February 17, 2022. This application cites the above Chinese patent application in full.

[0002] [Technical field] The present invention relates to crystals, methods of preparation and uses of nitrogen-containing heterocyclic compounds. [Background technology]

[0003] Nitrogen-containing heterocyclic compound 1, whose chemical name is (R,Z)-N-(4-((4-([1,2,4]triazolo[1,5-a]pyridine-7-oxo)-3-toluene)amine)-7-ethoxyquinazolin-6-yl)-2-fluoro-3-(1-methylpyrrolidin-2-yl)acrylamide, has the molecular formula C 31 H 31 FN8O3, the structural formula of which is shown below.

[0004] [ka]

[0005] CN109422755 and WO2019042409 disclose the nitrogen-containing heterocyclic compounds and their preparation methods. Compound 1 prepared by the method disclosed in the patent is a yellow foamy solid with non-ideal solid-state properties. Compound 1 also shows that it is a small molecule inhibitor that weakens EGFR kinase inhibitory activity or is selective for ErbB2 target. Summary of the Invention

[0006] The technical problem to be solved by the present invention is to provide a crystal, preparation method and use of (R,Z)-N-(4-((4-([1,2,4]triazolo[1,5-a]pyridine-7-oxo)-3-toluene)amine)-7-ethoxyquinazolin-6-yl)-2-fluoro-3-(1-methylpyrrolidin-2-yl)acrylamide having high stability and good bioavailability, in order to overcome the drawback of the solid-state properties of the compound in the prior art being not ideal.

[0007] The present invention solves the above technical problems through the following technical solutions.

[0008] The present invention provides a C-type crystal of Compound 1.

[0009] [ka]

[0010] The C-type crystal has a powder X-ray diffraction pattern expressed as 2θ using Cu-Kα radiation, which has diffraction peaks at the following positions: 5.32±0.2°, 8.42±0.2°, 10.62±0.2°, 11.48±0.2°, 13.46±0.2°, 16.14±0.2°, 16.57±0.2°, 16.96±0.2°, 17.26±0.2° and 18.11±0.2°.

[0011] In one embodiment, the C-type crystal further has a powder X-ray diffraction pattern represented by 2θ angles at one or more of the following positions: 19.42±0.2°, 21.26±0.2°, 22.11±0.2°, 22.73±0.2°, 23.05±0.2°, 23.45±0.2°, 25.98±0.2°, 26.71±0.2°, 26.89±0.2°. and preferably has diffraction peaks at one or more of the following positions: 12.23±0.2°, 13.00±0.2°, 14.76±0.2°, 20.33±0.2°, 24.89±0.2°, 28.50±0.2°, 31.74±0.2°, 34.46±0.2°, 35.94±0.2° and 37.67±0.2°.

[0012] In one embodiment, the C-type crystal has a powder X-ray diffraction pattern expressed in 2θ angles having the characteristic diffraction peaks shown in the table below.

[0013] [Table 1]

[0014] In one embodiment, the powder X-ray diffraction pattern of the C-type crystal, expressed in terms of 2θ angles, is essentially as shown in FIG.

[0015] In one embodiment, the differential scanning calorimetry spectrum of the C-type crystals has one endothermic peak at 213.3° C. (onset temperature).

[0016] In one embodiment, the differential scanning calorimetry spectrum of the C-type crystals has one endothermic peak at 213.3° C. (onset temperature), and the heat of fusion is 95.16 J / g.

[0017] In one embodiment, the differential scanning calorimetry spectrum of the C-type crystals is essentially as shown in FIG.

[0018] In one embodiment, the thermogravimetric analysis spectrum of the C-type crystals shows that the weight decreases by 2.1% when heated to 200°C, and decreases by 1.5% when further heated to 230°C.

[0019] In one embodiment, the thermogravimetric analysis spectrum of the C-type crystals is essentially as shown in FIG.

[0020] The present invention further provides a method for producing the above C-type crystal, which is Scheme 1 or Scheme 2.

[0021] Scheme 1 includes a step of crystallizing a suspension of compound 1 and a solvent to obtain a C-type crystal of compound 1;

[0022]

change

[0023] The compound 1 is one of B-type crystals, A-type crystals, G-type crystals, H-type crystals, I-type crystals, M-type crystals and E-type crystals, and the B-type crystals have diffraction peaks at the following positions in the powder X-ray diffraction pattern represented by 2θ using Cu-Kα radiation: 7.53±0.2°, 8.83±0.2°, 12.72±0.2°, 13.98±0.2°, 14.20±0.2°, 15.05±0.2°, 15.44±0.2°, 17.68±0.2°, 18.13±0.2°, 18.38±0.2°, 18.86±0.2°, 21.24±0.2°, 22.44±0.2° and 24.54±0.2°. The A-type crystal has a powder X-ray diffraction pattern expressed as 2θ using Cu-Kα radiation, which has diffraction peaks at the following positions: 5.97±0.2°, 12.27±0.2°, 13.30±0.2°, 14.31±0.2°, 16.08±0.2°, 16.60±0.2°, 17.93±0.2°, and 20.24±0.2°. The G-type crystal has a powder X-ray diffraction pattern expressed as 2θ using Cu-Kα radiation, and has diffraction peaks at the following positions: 6.41±0.2°, 6.88±0.2°, 8.75±0.2°, 12.82±0.2°, 13.38±0.2°, 13.73±0.2°, 16.74±0.2°, 17.64±0.2°, 19.24±0.2°, 21.68±0.2°, 22.77±0.2°, 26.14±0.2°, and 26.49±0.2°. The H-type crystal has a powder X-ray diffraction pattern expressed by 2θ using Cu-Kα radiation, and has diffraction peaks at the following positions: 5.41±0.2°, 6.13±0.2°, 7.92±0.2°, 11.19±0.2°, 12.26±0.2°, and 21.91±0.2°. The I-type crystal has a powder X-ray diffraction pattern expressed by 2θ using Cu-Kα radiation, and has diffraction peaks at the following positions: 6.80±0.2°, 7.22±0.2°, 8.03±0.2°, 8.35±0.2°, 9.70±0.2°, 10.28±0.2°, and 19.84±0.2°.The M-type crystal has a powder X-ray diffraction pattern expressed as 2θ using Cu-Kα radiation, which has diffraction peaks at the following positions: 5.52±0.2°, 7.96±0.2°, 9.41±0.2°, 13.36±0.2°, 14.68±0.2°, 17.93±0.2°, 18.70±0.2°, 25.75±0.2°, 26.11±0.2°, and 26.50±0.2°. The E-type crystal has a powder X-ray diffraction pattern expressed as 2θ using Cu-Kα radiation, which has diffraction peaks at the following positions: 6.07±0.2°, 8.97±0.2°, 9.32±0.2°, 9.87±0.2°, 13.05±0.2°, 13.27±0.2°, 14.09±0.2°, 15.78±0.2°, 16.98±0.2°, 18.27±0.2°, 18.47±0.2°, 21.26±0.2°, and 22.41±0.2°.

[0024] When the compound 1 is one of A-type crystals, G-type crystals, H-type crystals, I-type crystals, M-type crystals and E-type crystals, the solvent is acetone or acetone / water.

[0025] When the compound 1 is a B-type crystal, the solvent is acetonitrile or ethanol.

[0026] Scheme 2 includes a step of crystallizing compound 1 in a solvent to obtain C-type crystals of compound 1, the solvent being an alcohol solvent, preferably ethanol or isopropanol.

[0027] In the method for producing the C-type crystal, when the scheme 1 is used and the solvent is acetone / water, the volume ratio of acetone to water is 986:14 to 950:50.

[0028] In the method for producing the C-type crystal, when the Scheme 1 is used and the compound 1 is one of the A-type crystal, the G-type crystal, the H-type crystal, the I-type crystal, the M-type crystal, and the E-type crystal, the crystallization temperature is 20 to 30°C (room temperature).

[0029] In the method for producing the C-type crystals, when the Scheme 1 is used and the compound 1 is a B-type crystal, the crystallization temperature is 20 to 50° C., for example, 20 to 30° C. (room temperature).

[0030] In the method for producing the C-type crystal, when the scheme 2 is used, the mass / volume ratio of the compound 1 to the solvent is 100 mg:2 mL.

[0031] In the method for producing the C-type crystals, when the Scheme 2 is used, the crystallization temperature is 50 to 60°C, and preferably 55°C.

[0032] In the method for producing the C-type crystals, when the scheme 2 is used, the crystallization time is 24 hours.

[0033] The present invention further provides a pharmaceutical composition comprising the above-mentioned C-type crystal and pharmaceutical auxiliary agents.

[0034] The present invention further provides use of the above-mentioned type C crystal in the manufacture of a medicament for treating cancer and / or a disease treated by inhibiting EGFR and / or ErbB2 receptor tyrosine kinase, for example, treating a disease treated by selective inhibition of ErbB2 receptor tyrosine kinase, wherein the cancer and the disease may be breast cancer, gastric cancer, ovarian cancer, lung cancer, etc., and the type C crystal may be in a therapeutically effective amount.

[0035] The present invention further provides use of the above-mentioned C-type crystal in the manufacture of an EGFR and / or ErbB2 receptor tyrosine kinase inhibitor. The EGFR and / or ErbB2 receptor tyrosine kinase inhibitor may be a selective ErbB2 receptor tyrosine kinase inhibitor.

[0036] In the present invention, "room temperature" refers to 20 to 30°C.

[0037] The above preferred conditions can be combined in any manner to obtain each preferred embodiment of the present invention without violating the ordinary skill in the art.

[0038] The reagents and materials used in the present invention are commercially available.

[0039] The positive effect of the present invention is to overcome the shortcomings of the non-ideal solid-state properties of (R,Z)-N-(4-((4-([1,2,4]triazolo[1,5-a]pyridine-7-oxo)-3-toluene)amine)-7-ethoxyquinazolin-6-yl)-2-fluoro-3-(1-methylpyrrolidin-2-yl)acrylamide in the prior art, and to provide a crystal of said compound with high stability and good bioavailability. [Brief description of the drawings]

[0040] [Figure 1] This is the XRPD pattern of type A crystals. [Diagram 2] This is the TGA / DSC pattern of A-type crystals. [Diagram 3] This is the XRPD pattern of B-type crystals. [Figure 4] This is a TGA / DSC pattern of B-type crystals. [Diagram 5] This is the XRPD pattern of C-type crystals. [Figure 6] This is a TGA / DSC pattern of C-type crystals. [Figure 7] This is the XRPD pattern of D-type crystals. [Figure 8] This is the XRPD pattern of E-type crystals. [Figure 9] This is a TGA / DSC pattern of E-type crystals. [Figure 10] This is the XRPD pattern of F-type crystals. [Figure 11] This is a TGA / DSC pattern of F-type crystals. [Figure 12] This is the XRPD pattern of G-type crystals. [Figure 13] This is a TGA / DSC pattern of G-type crystals. [Figure 14] This is the XRPD pattern of H-type crystals. [Figure 15] This is a TGA / DSC pattern of H-type crystals. [Figure 16] This is the XRPD pattern of type I crystals. [Figure 17] This is the TGA / DSC pattern of type I crystals. [Figure 18] This is the XRPD pattern of J-type crystals. [Figure 19] This is the XRPD pattern of K-type crystals. [Figure 20] This is the XRPD pattern of L-type crystals. [Figure 21] This is the XRPD pattern of M-type crystals. [Figure 22] This is a TGA / DSC pattern of M-type crystals. [Diagram 23] FIG. 1 is a comparative XRPD diagram of suspension competition between B-type crystals and C-type crystals. [Figure 24] FIG. 1 is a comparative XRPD diagram of a mixed suspension competition of C / A / G / H / I / M / E type crystals. [Diagram 25] FIG. 1 is a comparative XRPD diagram of a stability test of C-type crystals. [Figure 26] This is an amorphous XRPD pattern. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0041] The present invention will be further described below with reference to examples, but the present invention is not limited to the scope of these examples.

[0042] The abbreviations used in the present invention are explained as follows:

[0043] XPRD - Powder X-ray Diffraction TGA-Thermogravimetric analysis DSC - Differential Scanning Calorimetry DVS - Dynamic Moisture Sorption Analysis The test conditions are as shown below.

[0044] XRPD The powder X-ray diffraction patterns described in this application were obtained using a PANalytical Empyrean type powder X-ray diffractometer and a PANalytical X'Pert 3 The data were collected using a powder X-ray diffraction instrument.

[0045] The parameters of the Empyrean type powder X-ray diffraction method are as shown below.

[0046] X-ray type: Cu, Kα Kα1(Å):1.540598;Kα2(Å):1.544426 Kα2 / Kα1 intensity ratio: 0.50 Voltage: 45 kilovolts (kV) Current: 40 milliamps (mA) Divergence slit: Automatic Scanning mode: Continuous Scanning range: 3.0~40.0 degrees Scan time per step: 17.780 seconds Step width: 0.0167 degrees PANalytical X'Pert 3 The parameters of the powder X-ray diffraction method are as shown below.

[0047] X-ray type: Cu, Kα Kα1(Å):1.540598;Kα2(Å):1.544426 Kα2 / Kα1 intensity ratio: 0.50 Voltage: 45 kilovolts (kV) Current: 40 milliamps (mA) Divergence slit: 1 / 16 degree Scanning mode: Continuous Scanning range: 3.0~40.0 degrees Scan time per step: 46.665 seconds Step width: 0.0263 degrees DSC The differential scanning calorimetry (DSC) data described in this application were obtained from TA Instruments Q200 and TA Instruments Q2000 differential scanning calorimeters, the instrument control software was Q Series, and the analysis software was Universal Analysis. Typically, 1-10 mg of sample was placed in a covered aluminum crucible (unless otherwise specified), and the sample was heated from room temperature to 300°C at a heating rate of 10°C / min under the protection of 50 mL / min of dry N2, while the TA software recorded the thermal changes of the sample during the heating process. In this application, the melting point is reported as the onset temperature.

[0048] TGA The thermogravimetric analysis (TGA) data described in this application was obtained from TA Instruments Q500 and TA Instruments Q5000 thermogravimetric analyzers, the instrument control software was Q Series, and the analysis software was Universal Analysis. Typically, 2-15 mg of sample was placed in a platinum crucible, and the sample was heated from room temperature to 400°C at a heating rate of 10°C / min under the protection of 50 mL / min of dry N2 using a split high-resolution detection method, and the TA software recorded the weight change of the sample during the heating process.

[0049] DVS The dynamic moisture sorption diagrams described in this application were collected on SMS Intrinsic and Intrinsic Plus dynamic moisture sorption instruments. The parameters of the dynamic moisture sorption test method described in this invention are as shown below.

[0050] Temperature: 25℃ Protective gas and flow rate: N2, 200ml / min dm / dt:0.002% / min Minimum DM / DT equilibration time: 10 minutes Maximum equilibration time: 180 minutes Relative humidity range: 0%RH~95%RH~0%RH Relative humidity gradient: 10% (0%RH~90%RH~0%RH), 5% (90%RH~95%RH and 95%RH~90%RH) Example of preparation of amorphous form of Compound 1: Example 1: The structure of Compound 1 is shown below, and its amorphous form was prepared with reference to Patent CN109422755 and Example 45 of WO2019042409. The amorphous is a yellow foamy solid with non-ideal solid-state properties, and its XRPD is shown in Figure 26.

[0051] [ka]

[0052] Example of crystal production: Example 1 (A-type crystal of compound 1) 100 mg of compound 1B type crystals were suspended in 1 mL of EtOAc at room temperature and stirred for 5 days to prepare a solid, the XRPD of which is shown in Figure 1. Its TGA and DSC patterns are shown in Figure 2, the TGA data shows that the crystal sample loses weight by 6.4% when heated to 200°C, and the DSC shows two endothermic peaks at 137.2°C and 214.7°C (peak temperatures), the results indicating that the obtained solid product is the A type crystal described in the present application.

[0053] [Table 2]

[0054] Example 2 (B-type crystals of compound 1) 100 mg of amorphous compound 1 was stirred in 1 ml of acetone at room temperature for 2 hours to crystallize. The powder X-ray diffraction data of the obtained solid is as shown in Table 2, its XRPD pattern is as shown in Figure 3, and its TGA / DSC is as shown in Figure 4. The sample was heated from room temperature to 100°C, the weight decreased by 0.7%, and then heated to 220°C, the weight decreased by 2.3%, and there was one endothermic peak at 165.2°C (initiation temperature), which was estimated to be the melting signal of the sample. The results show that the obtained solid product is the B-type crystal described in the present application.

[0055] [Table 3]

[0056] Example 3 (C-type crystals of compound 1) 100 mg of amorphous compound 1 was crystallized by stirring in 2 ml of ethanol at 50-60°C for 24 hours. The powder X-ray diffraction data of the obtained solid was as shown in Table 3, its XRPD diagram was as shown in Figure 5, and the TGA / DSC result was as shown in Figure 6. The sample was heated from room temperature to 200°C, the weight decreased by 2.1%, and then heated to 230°C, the weight decreased by 1.5%, and there was one endothermic peak at 213.3°C (initiation temperature), which was estimated to be the signal of melting of the sample, and the heat of fusion was 95.16 J / g. The results show that the obtained solid product is the C-type crystal described in the present application.

[0057] [Table 4]

[0058] Example 4 (D-type crystal) 5 mg of amorphous compound 1 was crystallized in 1 ml of 2-methyltetrahydrofuran (2-MeTHF) by stirring at 50° C. for 4 days. The powder X-ray diffraction data of the obtained solid is shown in Table 4, and its XRPD diagram is shown in FIG. 7. The results show that the obtained solid product is the D-type crystal described in the present application.

[0059] [Table 5]

[0060] Example 5 (E-type crystal) 100 mg of B-type crystals of compound 1 were suspended and stirred in 1 mL of acetone / HO (605:395, v / v) at room temperature for 3 days, and repeatedly prepared. The powder X-ray diffraction data of the obtained solid is as shown in Table 5, its XRPD pattern is as shown in Figure 8, and the TGA / DSC result is as shown in Figure 9. The sample was heated from room temperature to 135°C, and showed a weight loss of 6.0% and two endothermic peaks at 85.8°C (peak temperature) and 160.0°C (peak temperature). The results showed that the obtained solid product was the E-type crystals described in this application.

[0061] [Table 6]

[0062] Example 6 (F-type crystal) 2 mg of B-type crystals of compound 1 were suspended and stirred in 1 mL of acetone / HO (605:395, v / v) at room temperature for 1 day. The powder X-ray diffraction data of the solid obtained is shown in Table 6, its XRPD pattern is shown in Figure 10, and the TGA / DSC result is shown in Figure 11. The sample was heated from room temperature to 140°C, and the weight of the sample decreased by 13.2%. There was one endothermic peak at 80.7°C (onset temperature). The results showed that the obtained solid product was the F-type crystals described in this application.

[0063] [Table 7] JPEG2025505801000013.jpg44169

[0064] Example 7 (G-type crystal) Weigh out 100mg of B-type crystals of compound 1, add 21mL of CHCl3 / MeOH (1:20, v / v) to dissolve the sample, filter the sample, seal with parafilm, make some small holes, place in a fume hood and allow to evaporate naturally at room temperature. The powder X-ray diffraction data of the obtained solid is as shown in Table 7, its XRPD diagram is as shown in Figure 12, and the TGA / DSC result is as shown in Figure 13. The sample is heated from room temperature to 125°C, the weight of the sample is reduced by 9.6%, and it shows two endothermic peaks at 83.0°C and 146.6°C (peak temperature), and the results show that the obtained solid product is the G-type crystals described in this application.

[0065] [Table 8]

[0066] Example 8 (H-type crystal) 100 mg of B-type crystals of compound 1 were suspended and stirred in 1 mL of water at 50°C for 4 days to produce a solid. The powder X-ray diffraction data of the solid are shown in Table 8, its XRPD pattern is shown in Figure 14, and the TGA / DSC result is shown in Figure 15. The sample was heated from room temperature to 150°C, and the weight of the sample decreased by 15.3%. The DSC result showed that the sample had one endothermic peak at 83.7°C (peak temperature). The result indicated that the obtained solid product was the H-type crystals described in the present application.

[0067] [Table 9]

[0068] Example 9 (I-type crystal) Weigh out 100mg of B-type crystals of compound 1, add 8mL of CHCl3 / IPA (1:3, v / v) to dissolve the sample, filter the sample, seal with parafilm, make some small holes, and place in a fume hood to evaporate naturally. The powder X-ray diffraction data of the obtained solid is as shown in Table 9, its XRPD pattern is as shown in Figure 16, and the TGA / DSC result is as shown in Figure 17. The sample is heated from room temperature to 150°C, and the weight decreases by 15.2%, and the DSC result shows that there is one endothermic peak at 95.5°C (peak temperature), and the result indicates that the obtained solid product is the I-type crystals described in this application.

[0069] [Table 10] JPEG2025505801000017.jpg95169

[0070] Example 10 (J-type crystal) 0.2mL dimethyl sulfoxide (DMSO) was added to 20mg of B-type crystals of compound 1 to dissolve the sample, the obtained sample was filtered, 5mL MIBK (4-methyl-2-pentanone) was added dropwise to the flask under magnetic stirring, the sample was evaporated at room temperature until a solid was formed, the powder X-ray diffraction data of the obtained solid was as shown in Table 10, and its XRPD diagram was as shown in Figure 18, the result showed that the obtained solid product was the J-type crystals described in this application.

[0071] [Table 11]

[0072] Example 11 (K-type crystal) Weigh out 100 mg of B-type crystals of compound 1, add 20 mL of CHCl3 / MeOH (1:20, v / v) to dissolve the sample, filter the sample, and evaporate at room temperature until a solid is formed. The powder X-ray diffraction data of the obtained solid is as shown in Table 11, and its XRPD pattern is as shown in Figure 19. The results show that the obtained solid product is the K-type crystals described in the present application.

[0073] [Table 12]

[0074] Example 12 (L-type crystal) The E-type crystals obtained in Example 5 were purged with nitrogen gas for 10 minutes, and the powder X-ray diffraction data of the obtained solid was as shown in Table 12, and its XRPD pattern was as shown in Figure 20. The results show that the obtained solid product is the L-type crystals described in the present application.

[0075] [Table 13]

[0076] Example 13 (M-type crystal) 100 mg of B-type crystals of compound 1 were suspended and stirred in 1 mL of acetone / HO (605:395, v / v) at room temperature for 6 days. The powder X-ray diffraction data of the solid obtained is shown in Table 13, its XRPD pattern is shown in Figure 21, and the TGA / DSC result is shown in Figure 22. The sample was heated from room temperature to 135°C, and the weight of the sample decreased by 6.9%. It showed two endothermic peaks at 81.6°C (onset temperature) and 157.6°C (onset temperature). The results showed that the obtained solid product was the M-type crystals described in the present application.

[0077] [Table 14]

[0078] Examples of crystal transformation Example 1 Suspension competition test of B-type crystals and C-type crystals The two crystals were subjected to a suspension competition test in acetonitrile and ethanol at room temperature and 50°C, and the test results are summarized in Table 14. The specific steps are as follows:

[0079] 1) preparing saturated solutions of B-type crystals in acetonitrile and ethanol at room temperature and 50°C, respectively, and filtering the solutions; 2) adding about 5 mg of B-type crystals and C-type crystals to 0.5 mL of each saturated solution: ethanol and acetonitrile solutions of B-type crystals, and suspending and stirring the resulting suspensions at room temperature and 50° C. for 2 days, respectively; 3) The solid test XRPD obtained after separation is shown in FIG.

[0080] Example 2 Suspension competition test of C / A / G / H / I / M / E type crystals C / A / G / H / I / M / E crystals were subjected to suspension competition tests in acetone or acetone with different volume ratios of acetone / H2O mixed solution (986 / 14, v / v and 950 / 50, v / v) at room temperature, and the test results are summarized in Table 14. The specific steps are as follows:

[0081] 1) preparing a saturated solution of C / A / G / H / I / M / E type crystals in each solvent reaction system under room temperature and filtering the same; 2) adding about 5 mg of C / A / G / H / I / M / E type crystals to 0.5 mL of each saturated solution, and suspending and stirring the resulting suspension at room temperature overnight; 3) The solid test XRPD obtained after separation is shown in FIG.

[0082] [Table 15]

[0083] Conclusion: According to the XRPD comparison results in Figures 23 and 24, the solid samples obtained in each reaction system were all C-type crystals, and it was inferred that C-type crystals are more stable crystals.

[0084] Evaluation of the physicochemical stability of C-type crystals Example 1 To evaluate the physicochemical stability of the C-type crystals, about 20 mg of each C-type crystal of compound 1 was weighed out, and left at 60°C in a sealed state for 1 day, and left at 25°C / 60% RH and 40°C / 75% RH in an open state (sealed with parafilm, with some holes in the parafilm) for 1 week. The solid samples placed under different conditions were tested for purity by UPLC to evaluate the chemical stability, and the crystals were tested by XRPD to evaluate the physical stability. The evaluation results are summarized in Table 15: under the three test conditions, no crystal transformation occurred in any of the C-type crystals, and the XRPD results are shown in Figure 25, and the samples were left at 60°C for 1 day, and left at 25°C / 60% RH and 40°C / 75% RH for 1 week, and no significant decomposition (specific purity changes are shown in Table 16).

[0085] [Table 16]

[0086] [Table 17]

[0087] Conclusion: Form C crystals showed good physicochemical stability after being left at 60°C for 1 day, and at 25°C / 60% RH and 40°C / 75% RH for 1 week.

[0088] Effect Example 1 Comparison of absorption in the body of rats administered different crystals Different crystals were administered intragastrically to SD rats, and 0.4 mL of blood was collected from the rat fundus venous plexus before and after administration at 5, 15, 30, 60, 90, 120, 240, 360, 480, 600, and 1440 minutes, respectively. The blood samples were centrifuged at 8000 rpm for 5 minutes to separate the upper layer of plasma, and 50 μL of plasma samples were added with 300 μL of acetonitrile containing internal standard (Propranolol, 25 ng / ml) to precipitate proteins, vortexed for 10 minutes, centrifuged at 6000 g and 4 °C for 20 minutes, 20 μL of the supernatant was taken, diluted with 80 μL of ultrapure water, centrifuged, and 80 μL of the supernatant was injected into a 96-well plate. The plasma drug concentrations obtained were detected by LC / MS / MS, and the corresponding pharmacokinetic parameters were calculated, as shown in Table 17.

[0089] [Table 18]

[0090] Conclusion: In this experiment, amorphous, A-type, B-type, C-type and M-type crystals were intragastrically administered to rats at a dose of 8 mg / kg, and the results showed that C-type crystal had the best pharmacokinetic parameters.

[0091] Effect Example 2 EGFR / ErbB2 enzyme experiment First, the 1x reaction buffer required for kinase was prepared, and the 5x enzyme buffer (20mM HEPES PH7.0, 0.1% NaN3, 0.05% BSA, 0.5mM sodium orthovanadate) of the HTRF kinEASE-TK kit was diluted to 1x using deionized water, and 50nM Supplement enzyme buffer (SEB reagent), 1mM MnCl2, 5mM MgCl2, and 1mM DTT were added at the same time. Step 2 was to prepare the 5x compound, and a stock solution of 10mM of the test compound (C-type crystal obtained in Example 3) was taken, and the compound was diluted in multiple steps using DMSO in a 96-well compound plate to obtain an initial concentration of 100x of the compound, and then the compound of that concentration was used as the first concentration, and a 3-fold gradient dilution was performed using DMSO to dilute to a total of 10 concentrations. Next, 1μl of each gradient dilution solution was added to 19μl of the 1x reaction buffer, and prepared as the 5x compound. Then, 2 μl of 5× compound was transferred from the 96-well plate to the 384-well plate. 2 μl of the following was added to the compound-free control wells: 1 μl of DMSO plus 19 μl of 1× reaction buffer. 2 μl of 250 mM EDTA was added to the blank control wells. In step 3, the enzyme reaction step, the kinase, substrate (TK Substrate-biotin), and ATP were prepared into 2.5× enzyme / substrate mixed solution and 2.5× ATP solution, respectively, using 1× reaction buffer. The final concentration of ErbB2 kinase (Sigma E2645-500UN) was 0.06ng / μl, the final concentration of ATP was 4μM, the final concentration of EGFR kinase (Carna 08-016) was 0.06units / μl, the final concentration of ATP was 1.65μM, 4μl of 2.5× enzyme / substrate mixed solution was added to a 384-well plate and incubated at room temperature for 5 minutes, and then 4μl of 2.5× ATP solution was added to each well and reacted at room temperature for 30 minutes. In the reaction stop step 4, a 2× TK Antibody-Eu(K) and Sa-XL665 mixed solution was prepared using HTRF Detection buffer, and the dose of TK Antibody-Eu(K) was 5μl per detection well.After carrying out the enzyme reaction for 30 minutes, 10 μl of the above liquid was added to the 384-well plate and reacted at room temperature for 1 hour. Data measurement was carried out using EnVisionTM, a laser with a wavelength of 337 nM was used as the excitation light, RFU665 nM and RFU620 nM were measured, and RFU665 nM / RFU620 nM × 10,000 was analyzed as the final data.

[0092] [Table 19]

[0093] Although the specific embodiments of the present invention have been described above, those skilled in the art should understand that these are merely examples, and the scope of protection of the present invention is limited by the appended claims. Those skilled in the art can make various changes or modifications to these embodiments without departing from the principle and essence of the present invention, and all such changes or modifications are within the scope of protection of the present invention.

Claims

1. A powder X-ray diffraction pattern expressed as 2θ using Cu-Kα radiation is characterized by having diffraction peaks at the following positions: 5.32±0.2°, 8.42±0.2°, 10.62±0.2°, 11.48±0.2°, 13.46±0.2°, 16.14±0.2°, 16.57±0.2°, 16.96±0.2°, 17.26±0.2°, and 18.11±0.2°. A C-type crystal of Compound 1. 【Chemistry 1】

2. The C-type crystal is (1) The powder X-ray diffraction pattern of the C-type crystals, expressed by 2θ angles, further includes diffraction peaks at one or more of the following positions: 19.42±0.2°, 21.26±0.2°, 22.11±0.2°, 22.73±0.2°, 23.05±0.2°, 23.45±0.2°, 25.98±0.2°, 26.71±0.2°, and 26.89±0.2°. and preferably further having diffraction peaks at one or more of the following positions: 12.23±0.2°, 13.00±0.2°, 14.76±0.2°, 20.33±0.2°, 24.89±0.2°, 28.50±0.2°, 31.74±0.2°, 34.46±0.2°, 35.94±0.2°, and 37.67±0.2°; (2) The differential scanning calorimetry spectrum of the C-type crystals has one endothermic peak at 213.3°C; (3) The thermogravimetric analysis spectrum of the C-type crystal shows a weight loss of 2.1% when heated to 200° C., and a weight loss of 1.5% when continuously heated to 230° C.; The C-type crystal according to claim 1, characterized in that it satisfies one or more of the following conditions.

3. The C-type crystal is (1) The condition that the powder X-ray diffraction pattern of the C-type crystal expressed by 2θ angles has the target diffraction peaks shown in the following table, 【Table 1】 (2) The differential scanning calorimetry spectrum of the C-type crystals has one endothermic peak at 213.3°C and a heat of fusion of 95.16 J / g; (3) The thermogravimetric analysis spectrum of the C-type crystal is essentially as shown in FIG. 6; The C-type crystal according to claim 2, characterized in that it satisfies one or more of the following conditions.

4. The C-type crystal is (1) The powder X-ray diffraction pattern of the C-type crystals, expressed by 2θ angles, is essentially as shown in FIG. 5; (2) The differential scanning calorimetry spectrum of the C-type crystal is essentially as shown in FIG. 6; The C-type crystal according to claim 3, which satisfies one or two of the following conditions.

5. Scheme 1, crystallizing a suspension of compound 1 and a solvent to obtain C-type crystals of compound 1; 【Chemistry 2】 The compound 1 is selected from B-type crystals, A-type crystals, G-type crystals, H-type crystals, I-type crystals, M-type crystals and E-type crystals, and the B-type crystals have a powder X-ray diffraction pattern represented by 2θ using Cu-Kα radiation at the following positions: 7.53±0.2°, 8.83±0.2°, 12.72±0.2°, 13.98±0.2°, 14.20±0.2°, 15.05±0.2°, 15.44±0.2°, 17.68±0.2°, 18.13±0.2°, 18.38±0.2°, 18.86±0.2°, 21.24±0.2°, 22.44±0.2° and 24.54±0.2°. The A-type crystal has a powder X-ray diffraction pattern represented by 2θ using Cu-Kα radiation, and has diffraction peaks at the following positions: 5.97±0.2°, 12.27±0.2°, 13.30±0.2°, 14.31±0.2°, 16.08±0.2°, 16.60±0.2°, 17.93±0.2°, and 20.24±0.2°. The G-type crystal has a powder X-ray diffraction pattern represented by 2θ using Cu-Kα radiation, and has diffraction peaks at the following positions: 6.41±0.2°, 6.88±0.2°, 8.75±0.2°, 12.82±0.2°. , 13.38±0.2°, 13.73±0.2°, 16.74±0.2°, 17.64±0.2°, 19.24±0.2°, 21.68±0.2°, 22.77±0.2°, 26.14±0.2° and 26.49±0.2°. The H-type crystal has a powder X-ray diffraction pattern represented by 2θ using Cu-Kα radiation, which has diffraction peaks at the following positions: 5.41±0.2°, 6.13±0.2°, 7.92±0.2°, 11.19±0.2°, 12.26±0.2° and 21.91±0.2°. The I-type crystal has a powder X-ray diffraction pattern represented by 2θ using Cu-Kα radiation, which has diffraction peaks at the following positions: 5.41±0.2°, 6.13±0.2°, 7.92±0.2°, 11.19±0.2°, 12.26±0.2° and 21.91±0.2°. The powder X-ray diffraction pattern expressed by 2θ using Cu-Kα radiation has diffraction peaks at the following positions: 6.80±0.2°, 7.22±0.2°, 8.03±0.2°, 8.35±0.2°, 9.70±0.2°, 10.28±0.2°, and 19.84±0.2°. The M-type crystal has a powder X-ray diffraction pattern expressed by 2θ using Cu-Kα radiation has diffraction peaks at the following positions: 5.52±0.2°, 7.96±0.2°, 9.41±0.2°, 13.36±0.2°, 14.68±0.2°, 17.93±0.2°, 18.70±0.2°, 25.75±0.2°.The E-type crystal has diffraction peaks at 26.11±0.2° and 26.50±0.2°, and the E-type crystal has a powder X-ray diffraction pattern represented by 2θ using Cu-Kα radiation, which has diffraction peaks at the following positions: 6.07±0.2°, 8.97±0.2°, 9.32±0.2°, 9.87±0.2°, 13.05±0.2°, 13.27±0.2°, 14.09±0.2°, 15.78±0.2°, 16.98±0.2°, 18.27±0.2°, 18.47±0.2°, 21.26±0.2°, and 22.41±0.2°, when the compound 1 is selected from the group consisting of A-type crystals, G-type crystals, H-type crystals, I-type crystals, M-type crystals, and E-type crystals, the solvent is acetone or acetone / water; When the compound 1 is a B-type crystal, the solvent is acetonitrile or ethanol; or Scheme 2, The method includes a step of crystallizing compound 1 in a solvent to obtain a C-type crystal of compound 1, wherein the solvent is an alcohol solvent, preferably ethanol or isopropanol; A method for producing the C-type crystal according to any one of claims 1 to 4.

6. In Scheme 1, the method comprises the steps of: (1) When the solvent is acetone / water, the volume ratio of acetone to water is 986:14 to 950:50; (2) When the compound 1 is one of A-type crystals, G-type crystals, H-type crystals, I-type crystals, M-type crystals, and E-type crystals, the crystallization temperature is 20 to 30° C.; (3) When the compound 1 is a B-type crystal, the crystallization temperature is 20 to 50° C., for example, 20 to 30° C.; The method for producing a C-type crystal according to claim 5, characterized in that one or more of the following conditions are satisfied.

7. In Scheme 2, the method comprises the steps of: (1) The mass / volume ratio of the compound 1 to the solvent is 100 mg:2 mL; (2) The crystallization temperature is 50 to 60° C., preferably 55° C.; (3) The crystallization time is 24 hours; The method for producing a C-type crystal according to claim 5, characterized in that one or more of the following conditions are satisfied.

8. A pharmaceutical composition comprising the C-type crystal according to any one of claims 1 to 7 and pharmaceutical auxiliary agents.

9. Use of the C-type crystal described in any one of claims 1 to 7 in the manufacture of a medicament for treating cancer and / or a disease treated by inhibiting EGFR and / or ErbB2 receptor tyrosine kinase, for example, treating a disease treated by selective inhibition of ErbB2 receptor tyrosine kinase, the cancer and the disease may be breast cancer, gastric cancer, ovarian cancer, lung cancer, and the C-type crystal may be in a therapeutically effective amount.

10. Use of the C-type crystal described in any one of claims 1 to 7 in the manufacture of an EGFR and / or ErbB2 receptor tyrosine kinase inhibitor, wherein the EGFR and / or ErbB2 receptor tyrosine kinase inhibitor may be a selective ErbB2 receptor tyrosine kinase inhibitor.